Immunotherapy With Programmed Cell Death 1 Inhibitors for 5 Patients With Conjunctival Melanoma - Sagiv, Oded; Thakar, Sudip D; Kandl, Thomas J; Ford, Joshua; Sniegowski, Matthew C; Hwu, Wen-Jen; Esmaeli, Bita (JAMA ophthalmology, 2018)
Conjunctival melanoma has the potential for regional lymphatic and distant metastasis. There is an urgent need for effective treatment for patients with metastatic or locally advanced conjunctival melanoma. To describe the use of immune checkpoint inhibitors for the treatment of conjunctival melanoma in 5 adult patients. A retrospective review was conducted of the medical records of 5 patients with conjunctival melanoma who were treated with immune checkpoint inhibitors from March 6, 2013, to July 7, 2017. Response to treatment and disease-free survival. Of the 5 patients (4 women and 1 man) with metastatic conjunctival melanoma, 4 were treated with a programmed cell death 1 (PD-1) inhibitor, nivolumab, and had a complete response to treatment with no evidence of disease at 1, 7, 9, and 36 months after completing treatment. One patient with metastatic conjunctival melanoma was treated with another PD-1 inhibitor, pembrolizumab, and had stable metastases during the first 6 months of treatment. Later disease progression resulted in treatment cessation after 11 months and switching to another therapy. Two patients treated with nivolumab developed autoimmune colitis that necessitated stopping the immunotherapy; these patients subsequently were managed with systemic corticosteroids or infliximab. This case series report suggests that anti-PD-1 therapy can be used to treat metastatic conjunctival melanoma. Longer follow-up is needed to determine the long-term disease-free survival. Future studies might assess the potential for immune checkpoint inhibitors to obviate the need for orbital exenteration in selected patients with locally advanced disease.